Rheumatoid Arthritis of Knee Joints: MRI–Pathological Correlation - Meng, Xiang‐hong (Orthop Surg, 2018)
OBJECTIVE: To evaluate the correlation between features of knee joint rheumatoid arthritis (RA) identified on MRI and histological examination as a means of elucidating the pathogenesis of joint destruction in RA. METHODS: This is a prospective analysis of 26 knee joints of 22 patients who underwent total knee arthroplasty (TKA) for the treatment of RA. Based on the degree of destruction of articular cartilage and the menisci, the occurrence of bone marrow edema and bone erosion, and synovial thickening, the stage of the knee joints were classified using MRI by two radiologists. Differences in the severity of destruction of the articular cartilage of the medial and lateral femoral condyles and medial and lateral tibial plateaus, the medial and lateral menisci, and bone were compared using analysis of variance with a post‐hoc test, and the Mann–Whitney U‐test. Samples of cartilage, subchondral bone, menisci, and synovium were obtained from the resected knee specimens during TKA and analyzed semiquantitatively using microscopy and immunohistochemistry. Histological differences between areas of bone erosion and bone marrow edema were evaluated using a Mann–Whitney U‐test. RESULTS: The extent of articular destruction was classified as grade 4 for the medial and lateral femoral condyles and the medial and lateral tibial plateaus for most patients, with an average destruction grade of 3.6 (F = 5.455, P = 0.002), with the least amount of destruction identified on the lateral femoral condyle. The majority of knee joints in the RA patients were at stage 3 (21/26, 80.8%), followed by stage 4 (4/26, 15.4%). Fibrosis, thinning and destruction, and hyperplasia were the most severe pathological changes in cartilage. In a total of 26 specimens, 36 areas of bone marrow edema and 68 areas of bone erosion were identified, with fibrosis, a mosaic structure of bone, and lymphocyte infiltration being the most severe changes in these areas. The degree of meniscus destruction was classified as grade 4 in the majority patients for both the medial and lateral meniscus, with an average degree of meniscal destruction over all specimens of 3.85, and greater destruction of the medial meniscus than of the lateral meniscus (Z = 2.062, P = 0.039). Fibrosis and engulfing calcified debris were the most severe pathological manifestations. Synovitis was also identified in all 26 specimens, with hyperplasia of intima cells and lymphocyte and plasma cell infiltration being the most severe pathological manifestations. CONCLUSIONS: Severe destruction of the articular cartilage and menisci is a characteristic feature of RA. Bone marrow edema and bone erosion can both also be found, but are less characteristic. Synovial infiltration may be the triggering mechanism of the destruction of the cartilage, menisci, and bone marrow. However, the origin of bone marrow edema requires further investigation.